Methods for droplet size distribution determination of water-inoil emulsions using low-field NMR - Opedal, Nils van der Tuuk; Sørland, Geir; Sjöblom, Johan (Diffusion Fundamentals, 2009)
A method using Pulsed Field Gradient Nuclear Magnetic Resonance PFG-NMR for water-incrude oil emulsion droplet size determination has been optimized and compared with optical microscope for validation. The method applies a combination of Pulsed-Field Gradient (PFG) NMR, Stimulated Echo (STE), and Carr-Purcell-Meimboom-Gill (CPMG) sequences for measuring diffusion, resolving oil and water signal and for measuring the attenuation due to a distribution in T2 values. This returns the droplet size distributions of water-in-oil emulsions within a minute. No prior assumption is made on the shape of the droplet size distribution, which enables the method to resolve for instance bimodal distributions. To validate this method, three different crude oils were used in the experiment. The emulsions prepared had water cuts from 10 to 40 %. The correlation between PFG-NMR and optical microscopy was good for the emulsions. Any potential discrepancies between the two techniques are discussed, so are the limitations and advantages of the methods.